ETYMOLOGY, THEORY, CONCEPTUALIZATION AND THE DIMENSION OF GLOBALIZATION - Zvarych, Roman (Journal of European Economy, 2017)
Etymology of globalization is established; its definitive apparatus is characterized and differs from westernization. The technography of origin and formation of the globalization theory are analyzed; main areas of its research are systematized. Disagreement on the conceptualization of the phenomenon of globalization in understanding the causes, structure, logic and consequences of its development is characterized. Dimension of globalization is estimated; its basic criticisms are the premise justifying its alternative are formed.